FDA collaboration to improve safe use of fluoroquinolone antibiotics: an ex post facto matched control study of targeted short-form messaging and online education served to high prescribers - John Whyte; Scott Winiecki; Christina Hoffman; Kaushal Patel (Centro de Investigaciones y Publicaciones Farmaceuticas, 2020)
Objective: This ex post facto matched control study was conducted to evaluate the effect of targeted short-form messages or continuing medical education (CME) on fluoroquinolone prescribing among high prescribers. Methods: A total of 11,774 Medscape healthcare provider (HCP) members prescribing high volumes of fluoroquinolones were randomized into three segments to receive one of three unique targeted short-form messages, each delivered via email, web alerts, and mobile alerts. Some HCPs receiving targeted short-form messages also participated in CME on fluoroquinolone prescribing. A fourth segment of HCPs participated in CME only. Test HCPs were matched to third-party-provider prescriber data to identify control HCPs. We used prescriber data to determine new prescription volume; percentage (%) of HCPs with reduced prescribing; new prescription volume for acute bacterial sinusitis (ABS), uncomplicated urinary tract infection (uUTI), and acute bacterial exacerbations of chronic bronchitis in those with chronic obstructive pulmonary disease (ABECB-COPD). Open rates for emailed targeted short-form messages were also measured. Results: Targeted short-form messages and CME each resulted in significant new prescription volume reduction versus control. Combining targeted short-form messages with CME yielded the greatest percentage of test HCPs with reduced prescribing (80.1%) versus controls (76.2%; p<0.0001). New prescription volume decreased significantly for uUTI and ABS following exposure to targeted short-form messages, CME, or both. Targeted short-form messages containing comparative prescribing information with or without clinical context were opened at slightly higher rates (10.8% and 10.6%, respectively) than targeted short-form messages containing clinical context alone (9.1%). Conclusions: Targeted short-form messages and CME, alone and in combination, are associated with reduced oral fluoroquinolone prescribing among high prescribers.